Kualitas Hidup Wanita Menopause (Quality of Life Among Menopausal Women) - Dessy Irwienna Putri; Dwi Martiana Wati; Yunus Ariyanto (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
AbstractMenopause is a condition when woman’s menstrual period ends because ovaries stopproducing estrogen and progesteron. The deficiency of these hormones cause women havemenopausal symptoms that can decrease their quality of life. This study aimed to analyzethe quality of life among menopausal women. This was a cross sectional study. The sampleconsisted of 128 menopausal women and their age ranged 45-59 years old. Chi-square,Anova, and Independent Sample t Test were used to analyze the data. The result showedbetter quality of life was experienced by women who had high education, did exerciseregularly, didn’t have chronic disease, and had mild menopausal symptoms. According toquality of life domain, physical domain was better in women who had married, did exerciseregularly and had mild menopausal symptoms. Psychological domain was better in womenwho had high education, did exercise regularly and didn’t have chronic disease.Environmental domain was better in women who had high education, did exercise regularly,and had mild menopausal symptoms. Whereas, social domain was better in married women.Based on this study, menopausal women are adviced to do exercise regularly so their qualityof life can be improved.Keywords: menopausal women, quality of life